Treatment of Lung Cancer in the Elderly Patient - Weiss, Jared; Langer, Corey (Seminars in Respiratory and Critical Care Medicine, 2013)
The median age of presentation with lung cancer is 71, making the elderly the dominant subgroup. Although some elderly patients are frail, others have great physiological reserve. Geriatric assessment can clarify the specific strengths and weaknesses of older patients, improving management. This assessment should, at the minimum, encompass performance status, comorbidity, medications, level of independence in activities of daily living and instrumental activities of daily living, cognitive assessment, nutrition assessment, and assessment of social support. The fit elderly with localized disease should be offered curative resection; video-assisted thoracic surgery may be preferred over thoracotomy. Fit septuagenarians with node positive or > 4 cm primary tumors should then be considered for adjuvant chemotherapy. For less fit patients, the data on stereotactic radiosurgery indicate that it presents a viable treatment option. Data on stage III disease are limited but suggest that chemoradiotherapy, particularly when the chemotherapy is administered on a weekly schedule, is feasible in fit older patients. For the older patients with metastatic cancer, abundant tissue should be obtained at diagnosis to allow for comprehensive molecular characterization with the hopes of rendering the patient eligible for targeted therapy. When such a targeted therapy is not available, there is duration of life and quality of life benefit to the administration of cytotoxic chemotherapy. The standard of care for older patients with Eastern Cooperative Oncology Group (ECOG) performance status 0 to 2 is a platinum-based doublet. Prospective data on second-line therapy after failure of first-line therapy are limited but suggest a benefit to treatment.
Keywords: elderly; geriatric; geriatric assessment